2020
DOI: 10.1021/acsami.9b19570
|View full text |Cite
|
Sign up to set email alerts
|

Super-Slippery Degraded Black Phosphorus/Silicon Dioxide Interface

Abstract: The interfaces between two-dimensional (2D) materials and the silicon dioxide (SiO2)/silicon (Si) substrate, generally considered as a solid–solid mechanical contact, have been especially emphasized for the structure design and the property optimization in microsystems and nanoengineering. The basic understanding of the interfacial structure and dynamics for 2D material-based systems still remains one of the inevitable challenges ahead. Here, an interfacial mobile water layer is indicated to insert into the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 66 publications
2
47
1
Order By: Relevance
“…In addition, some illustrations of the excellent tribological properties of black phosphorus (BP) with the same 2D layered structure, as determined by previous researchers, also significantly aided this study [39][40][41][42]. The interaction between the nanoparticles and water contributed to the lubrication.…”
Section: Tribological Mechanism Of Nb 2 C Nanosheets With Different Dsupporting
confidence: 64%
“…In addition, some illustrations of the excellent tribological properties of black phosphorus (BP) with the same 2D layered structure, as determined by previous researchers, also significantly aided this study [39][40][41][42]. The interaction between the nanoparticles and water contributed to the lubrication.…”
Section: Tribological Mechanism Of Nb 2 C Nanosheets With Different Dsupporting
confidence: 64%
“…Several studies have confirmed the effectiveness of hard ceramic nanoparticles in improving the tribological properties of the coating, which is expected to enhance the adhesion of the transfer film to its counterpart [147]. Song and Zhang [70] found that the wear life increased from 1,250 to 2,750 m/μm for the PU composite coating with 3 wt% nano-silica and polytetrafluorowax (PFW), and the coefficient of friction slightly increased by 0.01.…”
Section: Tribological Properties Of Polymer Composite Coatingsmentioning
confidence: 93%
“…There are two main strategies for further enhancing the mechanical properties of polymer composites. First, the functionalization, using octa (aminophenyl) silsesquioxane, octadecylamine, fluoride, etc., is an efficient way [129][130][131][132][133][134][135], because both dispersion and stress transfer can significantly improve the strength. The functionalization of 2D nanomaterials is conducive to better dispersion [136].…”
Section: Strengthmentioning
confidence: 99%